Buying versus leasing fuel deposits for preservation - Thomas Eichner; Gilbert Kollenbach; Mark Schopf (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 2018)
In a two-period model with two groups of countries that extract, trade and consume fossil fuel, a climate coalition fights against climate damage by purchasing or leasing deposits to prevent their extraction, and seeks to manipulate the fuel prices in its favor. The deposit-purchase policy is inefficient since it leaves the first-period climate damage externality non-internalized, which is in stark contrast to the efficiency of the deposit-purchase policy in static models. However, for a subset of economies the deposit-lease policy turns out to be efficient. It internalizes the climate damage externalities and makes strategic action in the fuel markets ineffective. Finally, we compare the deposit-lease policy and the deposit-purchase policy in an empirically calibrated economy. If strategic action pays in the fuel markets, a transition from the deposit-purchase policy to the deposit-lease policy increases the coalition's welfare if the discount rate is small.
Keywords: F55; H23; Q54; Q58; 330; fossil fuel; deposit; deposit-lease policy; deposit-purchase policy; fuel cap